Drops and fibers — how biomolecular condensates and cytoskeletal filaments influence each other. Issue 3 (11th December 2020) - Wiegand, Tina; Hyman, Anthony A.
Abstract : The cellular cytoskeleton self-organizes by specific monomer–monomer interactions resulting in the polymerization of filaments. While we have long thought about the role of polymerization in cytoskeleton formation, we have only begun to consider the role of condensation in cytoskeletal organization. In this review, we highlight how the interplay between polymerization and condensation leads to the formation of the cytoskeleton.